Which is the correlation between carcinoid tumor and Laparoscopic Sleeve Gastrectomy? A case series and literature review. (December 2018) - Sista, Federico; Abruzzese, Valentina; Carandina, Sergio; Salvatorelli, Andrea; Furia, Marino Di; Cipolloni, Gianluca; Vicentini, Vincenzo; Guadagni, Stefano; Clementi, Marco
Abstract: Introduction: Gastric Carcinoid Tumors (GCT) are very rare in general population, but some studies evidenced a higher incidence among bariatric surgery patients. Laparoscopic Sleeve Gastrectomy (LSG) is a widely accepted procedure for the surgical treatment of morbid obesity. LSG acts both in reducing food intake and interfering with hormonal balance in the gut-brain axis. In these patients, incidental GCT diagnosis can occur both during pre-bariatric surgery investigation and during post-operative follow-up. Methods: We retrospectively analyzed the database of obesity patients submitted to LSG in two different centers to find out incidence of GCT in patients treated by surgery from May 2013 to March 2018. Results: From the 560 obese consecutive patients underwent LSG, we recorded two cases of patients with GCT (0.36%): the case 1 was a patient who had a pre-operative diagnosis of GTC receiving a curative LSG which totally included the carcinoid in the resected portion; the case 2 was a patient that received a curative endoscopic resection 42 months after LSG. Discussion: the predisposing factors that can correlate GCT with obesity and LSG and in particular the hormonal changes have been discussed. We illustrated our experience about the management of these tumors in obese patients. Conclusion: there are neither certain data which evidence a correlation between obesity and GCT, nor data to support the hypothesis of a higher incidence of GCT after bariatric surgery. Based on our experience in obese patients the finding of GCT in the pre-operatory phase is not an absolute contraindication for bariatric surgery. Highlights: Recent observations showed a high incidence of Gastric Carcinoid Tumor (GCT) in candidate patients for bariatric surgery. From a multicenter experience with Laparoscopic Sleeve Gastrectomy. We retrospectively recorded two GCT cases in obese patients (the first found out during pre-operative investigations and the second one detected 52 months after surgery). The possible correlations between obesity, LSG and GTC have been discussed.